Exposure to High Salinity During Seed Development Markedly Enhances Seedling Emergence and Fitness of the Progeny of the Extreme Halophyte Suaeda salsa - Guo, Jianrong; Du, Ming; Tian, Huaying; Wang, Baoshan (Frontiers in Plant Science, 2020)
Irrigation with 200 mM NaCl significantly increases vegetative and reproductive growth of the extreme halophyte Suaeda salsa. However, little is known about how the progeny of S. salsa plants grown under a continuous NaCl supply behave in terms of growth and seed set parameters. We investigated various plant growth and reproductive parameters of the progeny that germinated from seeds harvested from mother plants grown under 0 or 200 mM NaCl over three generations. Seedling emergence, plant height, stem diameter, total branch length, flowering branch length, flowering branch ratio, and seed production, were all significantly enhanced in the progeny produced by mother plants grown with 200 mM NaCl, compared to progeny of mother plants grown on low salinity conditions. Therefore, irrigation with 200 mM of NaCl is beneficial to seed development in the halophyte S. salsa, and possibly contributes to population establishment in high salinity environments. Likewise, the prolonged absence of NaCl in the growth environment inhibits seed development, results in lower seed quality and thus limits seedling growth of the progeny, thereby restricting S. salsa to a high salinity ecological niche.